Metformin combined with spironolactone vs. metformin alone in polycystic ovary syndrome: a meta-analysis - Zeng, Huamin; Zhang, Ying; Huang, Sikai; Wu, Jinghua; Ren, Wenrui; Zhou, Lingru; Huang, Leneng; Ye, Yuyin (Frontiers in Endocrinology, 2023)
Aims: Due to its high heterogenicity and unclear etiology, there is currently no specific treatment for polycystic ovary syndrome (PCOS). Metformin, as an insulin sensitizer, combined with spironolactone, an antiandrogen medication, may exert complementary effects on PCOS. We therefore performed a meta-analysis of trials in which metformin combined with spironolactone was applied to treat PCOS to evaluate the efficacy and safety of the combination therapy.: We etrieved the PubMed, Embase, Scopus, Cochrane Library, CNKI, CBM, Wangfang, and VIP databases for literatures published from their inception to December 16, 2022 on the effects of metformin combined with spironolactone in the treatment of PCOS. Inclusion criteria according to P.I.C.O.S criteria were: PCOS patients, metformin combined with spironolactone interventions, metformin alone control group, and randomized controlled trials with the following outcome data: body mass index (BMI), hirsutism score, luteinizing hormone (LH), follicle-stimulating hormone (FSH), total testosterone (TT), fasting blood glucose (FBG), Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), and side effects including nausea, vomiting, diarrhea and drug withdrawal.Results: Our results revealed that metformin combined with spironolactone significantly reduced BMI and TT, but that it exerted no significant effects on hirsutism score, or on FSH or LH concentrations. Combined treatment also resulted in a significant diminution in FBG and insulin resistance using the HOMA-IR when the interventional time was greater than 6 months. In addition, the combination did not have a higher occurrence of adverse reactions than metformin alone.Compared with metformin alone, metformin combined with spironolactone therapy may be more effective in reducing BMI and serum androgen levels, but the combination showed no significant effect on the hirsutism score or gonadotropin hormone levels, and was not associated with This is a provisional file, not the final typeset article an elevation in side-effects. Moreover, when the treatment course was greater than 6 months, combination therapy reduced FBG and improved insulin resistance more effectively than metformin alone. However, more research is needed to determine the most effective course of treatment.